Landscape, Time and the Philosophy of Michel Serres - Kelly, James (The Trumpeter, 2025)
This article explores the changing uses of the word landscape over time, using ideas from the philosophy of Michel Serres to examine the word’s relevance to contemporary debates on humans and nature. It begins by reflecting on the three types of domestication of the landscape (the farm, the garden, and the national park) identified in Serres’s introductory essay to a book to commemorate the fortieth anniversary of the Pyrenees National Park. These three figures provide a point of departure for an exploration of how the changing meanings of the word “landscape” in the English language reflect our position as humans with respect to nature. Using the geological metaphor of the stratigraphic column to look at different strata in the word’s history and the different meanings associated with it over time, the first part of the article examines how a specific usage of the word associated with each stratum reflects a certain way of seeing the world and the human position in it. Having thus grounded the term etymologically, the second part of the article examines how ideas from Serres’s The Incandescent embody a fundamental shift in how the human subject is conceived, providing a philosophical foundation for a new way of thinking about landscapes, advocating the importance of the concept for reflecting on the ecological challenges we face in the twenty-first century.